Screening criteria for retinopathy of prematurity in developing countries - ÖZEK, EREN; ŞAHİN, ÖZLEM (SAGE PUBLICATIONS LTD, 2010)
PURPOSE. Retinopathy of prematurity (ROP) is a serious problem which potentially can lead to blindness. The objective of this study is to detect the incidence of ROP and the number of preterm babies requiring treatment for ROP in our center and to establish the screening criteria for our country. METHODS. A total of 801 babies with a gestational age less than 37 weeks were screened for ROP. Babies with a gestational age (GA) less than 32 weeks (n=348) were assigned as group 1. Babies with a GA between 32 and 34 weeks (n=335) were assigned as group 2 and between 35 and 37 weeks (n=98) were assigned as group 3. Clinical features and ROP screening results of the cases were documented. RESULTS. In group 1, ROP was detected in 176 (50.9%) babies, 41 (11.8%) of whom were treated with laser/cryotherapy. In group 2, 83 (25%) cases of ROP were detected, and 11 of them (3.1%) required therapy. In group 3, 9 (9.1%) infants were diagnosed with ROP, and none of them required treatment. Clinical factors associated with ROP in group 1 were gestational age, birthweight, duration of ventilation, duration of oxygen supplementation, sepsis, and bronchopulmonary dysplasia. CONCLUSIONS. In developing countries, the criteria for ROP screening programs should be designed according to local conditions. In our country, screening all premature babies with a gestational age less than 34 weeks or a birthweight less than 1850 g appears to be appropriate. (Eur J Ophthalmol 2010; 20: 931-7)
Keywords: Developing country; Retinopathy of prematurity; Screening criteria; BLIND SCHOOL STUDENTS; CHILDHOOD BLINDNESS; CHILDREN; INDIA; CHINA